Analisis Kesulitan Menulis pada Peserta Didik Kelas 4 SD - Tia Rahma, Mulia; Arnez, Gaby (Indo-MathEdu Intellectuals Journal, 2025)
Writing is one of the essential skills that must be mastered by every elementary school student. This study aims to analyze writing difficulties and identify the factors that influence the writing ability of fourth-grade elementary school students. The research employed a qualitative descriptive method. Data were collected through observation, interviews, direct tests with students, and documentation. The data analysis technique used qualitative data analysis consisting of data reduction, data display, and conclusion drawing. The results of the analysis show that the writing difficulties experienced by fourth-grade students, as seen from their written work, include: letter forms that are difficult to recognize, mixing of uppercase and lowercase letters, omission or addition of letters in words, slow writing speed, and unclear or illegible handwriting. Furthermore, the factors causing writing difficulties include internal factors such as weak fine motor skills, poor memory ability, low learning interest, and learning habits practiced by students both at school and at home. External factors include a lack of parental attention, an unsupportive home environment, surrounding environmental conditions, and the influence of technology.